Enhanced Pro-Apoptotic Effect of Tetrandrine Loaded Nanoparticles Against Osteosarcoma Cells - Tian, Yong; Yin, Haitao; Xu, Huae (Current Drug Delivery, 2016)
Background: Tetrandrine (Tet), a kind of herbal medicine belonging to the family of bis-benzylisoquinoline alkaloid, has gained more attraction for its potential anti-tumor effects. However, its potential utilization in clinic is greatly hampered by the poor pharmacokinetcs profile due to its insolubility. Recently, biodegradable polymeric nanoparticles with amphilic copolymers as drug carriers have shown better bioavailability against tumor as promising tumor-targeted drug delivery system. Methods: In the current study, Tet-loaded nanoparticles (Tet-NPs) was prepared with amphiphilic block copolymer as drug carriers. The physiochemical characterization, in vitro and in vivo antitumor effect of nanoparticles were evaluated. Results: In vitro study demonstrated the superior cell inhibitory effect of Tet-NPs. Most importantly, the viability of cells exposed to Tet-NPs was significant lower than that of cells treated with free Tet at lower equivalent doses. Moreover, Tet- NPs induced apoptosis and inhibited the proliferation of cells more effectively than free did at the equivalent concentration. Western blot showed that the expression of anti-apoptotic protein Bcl-2, Bcl-XL was significantly promoted while the pro-apoptotic Bax was significantly inhibited by the treatment of Tet-NPs. Conclusion: Data from the current study suggested that Tet-NPs is a promising delivery nano-system for the treatment of osteosarcoma.
Keywords: Drug delivery